2020
DOI: 10.1186/s43163-020-00004-6
|View full text |Cite
|
Sign up to set email alerts
|

The developed Arabic version of the Hearing Handicap Inventory for the Elderly

Abstract: Background: Hearing impairment ranks third on the list of chronic health conditions of the elderly, after arthritis and hypertension. As average lifespans increase, it is likely that the proportion of people with hearing loss will also increase. The purpose of the study was to develop, standardize, and apply an Arabic version of the Hearing Handicap Inventory for the Elderly (HHIE). Results: The mean age of the 100 subjects included in the pretest was 64.92 ± 5.937 with age ranged from 60 to 84 years. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Variety is the corner stone for production process. Aly (2006), El-Bakary (2006) and Ismail et al (2006) found that genotypes differed significantly in root length, diameter and fresh weight, impurities, sucrose and purity percentages, as well as, top, root and sugar yields/fad, in both seasons. Abd El-Aal et al, (2010), revealed a significant variation in yield productivity and root quality among sugar beet varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Variety is the corner stone for production process. Aly (2006), El-Bakary (2006) and Ismail et al (2006) found that genotypes differed significantly in root length, diameter and fresh weight, impurities, sucrose and purity percentages, as well as, top, root and sugar yields/fad, in both seasons. Abd El-Aal et al, (2010), revealed a significant variation in yield productivity and root quality among sugar beet varieties.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires were presented and completed in Arabic. All participants completed the Hearing Handicap Inventory for elderly (HHIE) ( Ismail et al, 2020 ), which is a self-assessment tool containing 25 questions assessing the impact of hearing loss on the emotional and social-situational adjustments, before and after the auditory program. Each question had three answers; (1) yes, (2) sometimes or (3) no.…”
Section: Methodsmentioning
confidence: 99%